Stability and Efficacy of Live-Attenuated Vibrio harveyi Vaccines Under Different Storage Conditions in Zebrafish (Danio rerio) Models - Muhamad-Sofie, Mohd Hafiz Ngoo; Mohamad, Aslah; Azzam-Sayuti, Mohamad; Amal, Mohammad Noor Azmai; Zamri-Saad, Mohd; Monir, Md Shirajum; Md Yasin, Ina Salwany (Jurnal Ilmiah Perikanan dan Kelautan, 2024)
Graphical Abstract Highlight Research The LD50 (median lethal dose) of Vibrio parahaemolyticus and harveyi in zebrafish was determined to be 1 x 106 CFU/mL, while for V. alginolyticus it was found to be 1 x 105 CFU/mL. The LAVh vaccine demonstrated cross-protection against various pathogenic strains of Vibrio, leading to an average of 80% survival rate in vaccinated individuals. The analysis of the LAVh vaccine emphasized its versatility, as it can be quickly deployed and stored as a freeze-dried powder. The LAVh vaccine can be easily accessible and user-friendly in various aquaculture environments, such as offshore and remote farms. Abstract Vibriosis poses a significant threat to marine teleosts, causing substantial losses in the global aquaculture industry. Previous work in our lab led to the development of a live-attenuated V. harveyi vaccine (LAVh) candidate that targets the serine endoprotease gene with a three-point knockout and has shown promise in protecting against vibriosis. However, further investigation is necessary to evaluate the stability and efficacy of its various storage conditions for broader applications. This study aims to determine how well the three different LAVh vaccine storage (fresh, stale, and freeze-dried LAVh) worked against vibriosis. A total of 1000 adult zebrafish (Danio rerio) (mean weight: 0.20±0.5 g) were divided into four groups. Groups 1, 2, and 3 were intraperitoneally injected with different LAVh vaccine storage (fresh, stale, and freeze-dried, respectively), while Group 4 received 0.01 M phosphate-buffered saline (PBS) and served as the unvaccinated control. Fish were monitored for 21 days post-vaccination for safety, stability, efficacy, and antibody analysis. The results showed that a modest dosage of 1 x 104 CFU/mL of LAVh vaccine from all storage conditions provided 80% survival upon intraperitoneal challenge with pathogenic strains of pathogenic V. harveyi, V. alginolyticus, and V. parahaemolyticus. This dosage induced significant antibody production and conferred cross-protection against different Vibrio spp., indicating the LAVh vaccine’s potential for commercial application. The LAVh vaccine demonstrated high effectiveness and suitability for storage as a freeze-dried powder. This study might offer significant insights into practical strategies for reducing vibriosis, especially in aquaculture settings with limited infrastructure.